The effect of synthesis conditions on the efficiency of C-S-H seeds to accelerate cement hydration. (March 2018) - Land, G.; Stephan, D.
Abstract: C-S-H seeding is a promising approach to accelerate cement hydration in a very effective way. Until now little is known about the way the C-S-H seeds work and how they affect the properties of the hydrated cement paste. To be able to analyse this in detail it is necessary to have a preparation method for the C-S-H seeds, which is reproducible and able to prepare seeds with defined properties. The present work describes two methods for the synthesis of C-S-H seeds, a mechanochemical approach and a sol-gel synthesis. A factorial design of experiments setup was used to find those parameters, which affect the efficiency of the C-S-H seeds to accelerate cement hydration and to adjust these parameters in order to achieve the optimized seeds, which are very effective accelerators. Heat flow calorimetry shows that the dormant period of cement hydration can be eliminated by the use of the optimized C-S-H seeds and compressive strength tests show a multiplication of early compressive strength even at very low concentrations of seeds, indicating that an optimization of the synthesis by factorial design of experiments is a promising way for further studies on the mode of action of C-S-H seeds.